Peran Organisasi IPNU Dalam Membina Akhlak Remaja Desa Rungkang Kecamatan Losari Kabupaten Brebes - Fakihuddin, Muhammad; T, Tosuerdi; Dinarni, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The IPNU organization is an autonomous body owned by the Islamic organization Nahdlatul Ulama, this organization is a forum for students and teenagers to serve at Nahdlatul Ulama, apart from that, this organization is a place for teenagers to develop themselves. IPNU is a learning organization that accommodates Nahdlatul Ulama youth. IPNU is not only required to strengthen ideology but also must respond to various challenges that arise. In IPNU there are positive activities that can have a positive influence on the moral condition of teenagers. This thesis is related to the moral development of Islamic teenagers, what is the role of the IPNU organization in developing the morals of teenagers in Rungkang village. With the aim of finding out how the morals of teenagers in Rungkang village are and the process of carrying out moral development which in the current era lacks moral education and monitoring from parents. This research is qualitative research whose technique is carried out by collecting relevant data through observation, interviews and documentation studies. The data obtained is expressed in written form which refers to the research results. Qualitative research tends to relate cause and effect phenomena. This research concludes that the morals of today's teenagers must be truly guided, because in this modern era, both positive and negative interactions very easily enter the lives of teenagers. Of course, with the presence of a community organization that houses teenagers, such as IPNU, it can become a forum for guiding teenagers through activities such as Yasinan, Tahlilan, and Koran studies. This effort is made to prevent teenagers from getting trapped in promiscuity so that teenagers' morals will be good, and conduciveness in society will be maintained.